1998
DOI: 10.1016/s0148-9062(98)00044-8
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Natural Rock Salt from the Waste Isolation Pilot Plant (WIPP) During Damage Evolution and Healing

Abstract: The U. S. Department of Energy has developed the Waste Isolation Pilot Plant (WIPP) in the bedded salt of southeastern New Mexico to demonstrate the safe disposal of radioactive transuranic wastes. Four vertical shafts provide access to the underground workings located at a depth of about 660 meters. These shafts connect the underground facility to the surface and potentially provide communication between lithologic units, so they will be sealed to limit both the release of hazardous waste from and fluid flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In laboratory tests Costin and Wawersik (1980), Brodsky (1990) and Pfeifle and Hurtado (1998) have shown that the damage evolution process in salt is reversible through crack closure and healing. In the Costin and Wawersik study, a series of short-rod fracture toughness strength tests were performed to determine the tensile load required to initiate and propagate fractures in WIPP salt.…”
Section: Salt Damage Healing In Laboratory Studiesmentioning
confidence: 99%
“…In laboratory tests Costin and Wawersik (1980), Brodsky (1990) and Pfeifle and Hurtado (1998) have shown that the damage evolution process in salt is reversible through crack closure and healing. In the Costin and Wawersik study, a series of short-rod fracture toughness strength tests were performed to determine the tensile load required to initiate and propagate fractures in WIPP salt.…”
Section: Salt Damage Healing In Laboratory Studiesmentioning
confidence: 99%
“…Hansen and Carter (1984) have carried out deformational experiments on very dry rocksalt from Avery Island Louisiana at elevated temperature and pressure both in constant stress mode and constant strain rate (Handin et al, 1986). Peach (1996), and Pfeifle and Hurtado (1998) have focused on the permeability of rocksalt under deformation. have proposed models which account for induced anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic conductivities of playa sediments are better known than ET g rates because desert playas are comprised of fine‐grained sediments and salts. Hydraulic conductivities of clay and salt are uncensored values well established from the literature (Czarnecki ; Pfeifle and Hurtado ; Garcia et al ; Huntington et al ). Simulated ET g rates from the DIXIE‐HYDK and DEATH‐HYDK models likely are more representative of actual ET g from the BSP and SEP ET units than the micrometeorological measurements.…”
Section: Resultsmentioning
confidence: 87%
“…Evaporation of unmeasured and unaccounted surface water inputs likely biased high BREB ET g rates from the BSP and SEP. Isolating the groundwater component of measured evaporation from BSP and SEP was complicated by surface water inundation during flooding events in 1998and 2001. DeMeo et al (2003 attempted to correct the measurement record for flooding periods based on indirect evidence; however, no attempt was made to account for changes in groundwater storage from infiltrating flood waters in either the unsaturated or saturated zone.…”
Section: Death Valley: Breb Approachmentioning
confidence: 99%